A Review on Properties, Opportunities, and Challenges of Transformer Oil-Based Nanofluids. (14th July 2016) - Rafiq, Muhammad; Lv, Yuzhen; Li, Chengrong
Abstract : The mineral oil or synthetic oil in conjunction with paper is mainly being applied as dielectric medium in many of the high voltage apparatus. However, the advent of high voltage levels such high voltage alternating current (HVAC) and high voltage direct current (HVDC) has prompted researchers to direct their focus onto an insulation system which can bear the rising high voltage levels. The modern insulating liquid material development is guided by various factors such as high electrical insulation requirements and other safety and economic considerations. Therefore transformer manufacturer companies have to design transformers with these new specific requirements. The transformer oil-based nanofluids with improved dielectric and thermal properties have the potential to replace mineral oil base products in the market place. They are favorable because they function more superior than mineral oil and they contribute definite insulating and thermal gains. This paper reviews recent status of nanofluids use as transformer oils. The nanofluids used as transformer oils are presented and their advantages are described in comparison with mineral oil. The multiple experimental works carried out by different researchers are described, providing an overview of the current research conducted on nanofluids. In addition scope and challenges being confronted in this area of research are clearly presented.